Walking the Walk: A Review of Medical Students' Perspective of a Surgical Theatre as the New Classroom - Tamara A. Mallia; Sarah Cuschieri (University Library System, University of Pittsburgh, 2023)
Medical school trains eligible students for a medical degree (MD). As part of the clinical years in the MD program, students attend surgical theatre sessions to learn medical concepts from hands-on experience in the theatre. This review aims to provide a comprehensive overview of the role surgical theatre plays in the learning process and clinical experience of medical students. Google Scholar, PubMed and NCBI databases were searched for articles from 1990 to March 2022 using the search terms 'Operating Room' or 'Operating Theatre' or 'Surgical Theatre' and 'Learning', 'Medical Students' and 'Surgeons'. Only articles on medical students' perceptions on their learning experience in the surgical theatre were included. Thirty-four articles were eligible for inclusion. Unpreparedness, anxiety, lack of clear learning outcomes, fear and intimidation were the most common reported experiences by students. These demotivate medical students from attending theatre, along with poor surgical field visibility, resulting in a negative learning experience. Positive experiences during theatre time were more likely to attract students to choose a future surgical career. Limitations include the inclusion of surgical residents' perspectives and the exclusion of other surgical team members' perspectives. Studies included students across different clinical years, and results were primarily based on subjective perceptions. Evidently, the surgical theatre is a great learning opportunity for medical students. However, for this learning environment to be beneficial, students need to be included during surgical discussions and procedures. Additionally, clear learning outcomes need to be present whilst adequately training students prior to their first surgical attendance.